2012
DOI: 10.4236/jilsa.2012.42010
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Bombay Stock Exchange (BSE) Market Returns Using Artificial Neural Network and Genetic Algorithm

Abstract: Stock Market is the market for security where organized issuance and trading of Stocks take place either through exchange or over the counter in electronic or physical form. It plays an important role in canalizing capital from the investors to the business houses, which consequently leads to the availability of funds for business expansion. In this paper, we investigate to predict the daily excess returns of Bombay Stock Exchange (BSE) indices over the respective Treasury bill rate returns. Initially, we prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…However, this does not infer that complicated structures of networks will always perform better (Perwej & Perwej, 2012). If the network has too many hidden neurons, it will follow the noise in the data due to over parameterization leading to poor generalization for untrained data (Subasi & Erçelebi, 2005).…”
Section: Artificial Neural Networkmentioning
confidence: 98%
See 1 more Smart Citation
“…However, this does not infer that complicated structures of networks will always perform better (Perwej & Perwej, 2012). If the network has too many hidden neurons, it will follow the noise in the data due to over parameterization leading to poor generalization for untrained data (Subasi & Erçelebi, 2005).…”
Section: Artificial Neural Networkmentioning
confidence: 98%
“…Stock market provides opportunities for brokers and companies to make investments on neutral ground and is one of the primary indicators of a economic condition of the country (Perwej & Perwej, 2012). However, stock market is characterized by nonlinearities, discontinuities, and high-frequency multi-polynomial components because it is interacted with many factors such as political events, general economic conditions, and traders' expectations (Hadavandi, Shavandi, & Ghanbari, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial Neural Networks (ANNs) is a common technique used in predicting financial time series analysis. [7] used the ANNs model to predict Bombay Stock Exchange (BSE) market returns using ANNs. They have found that ANNs model is more superior to the autoregressive model due to their ability to interpret both linear and nonlinear patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The prices of individual stocks can be affected by various factors e.g. economic growth (Perwej and Perwej, 2012;Selvin et al, 2017). It is difficult to analyse all factors manually (Nguyen et al, 2015;Sharma et al, 2017), so it would be better if there were tools for supporting the analysis of this data within a timely response.…”
Section: Introductionmentioning
confidence: 99%